Regulation of P2X2 Receptors by the Neuronal Calcium Sensor VILIP1 - Chaumont, Severine (2008)
Extracellular adenosine triphosphate (ATP) activates P2X receptors, which are involved in diverse physiological functions. Using a proteomic approach, we identified the neuronal calcium sensor VILIP1 as interacting with P2X2 receptors. We found that VILIP1 forms a signaling complex in vitro and in vivo with P2X2 receptors and regulates P2X2 receptor sensitivity to ATP, peak response, surface expression, and diffusion. VILIP1 constitutively binds to P2X2 receptors and displays enhanced interactions in an activation- and calcium-dependent manner owing to exposure of its binding segment in P2X2 receptors. VILIP1-P2X2 interactions are also enhanced in hippocampal neurons during conditions of action potential firing known to trigger P2X2 receptor activation. Our data thus reveal a previously unrecognized function for the neuronal calcium sensor protein VILIP1 and a mechanism for regulation of ATP-dependent P2X receptor signaling by neuronal calcium sensors.